Oesophageal lesions as first manifestation of necrotising sarcoid granulomatosis. (6th July 2015) - Attou, Rachid; Duttmann, Ruth; Devriendt, Arnaud; De Bels, David
Abstract : Necrotising sarcoid granulomatosis is a rare disease associating sarcoid-like granulomas, vasculitis and necrosis in the lungs and seldom in extrapulmonary locations. We report the case of a 23-year-old woman with an initial symptom consisting of epigastric pain. Oesophagoscopy demonstrated oesophagitis. Evolution was marked by fever, dyspnoea and pulmonary lesions. The first presumptive diagnosis was Wegener disease but biopsies (of the lungs and the oesophagus) demonstrated the diagnosis of necrotising sarcoid granulomatosis. Evolution was favourable under corticoid therapy. Necrotising sarcoid granulomatosis may present as an extrapulmonary disease and is an important differential diagnosis of other disease such as Wegener disease.